(untitled) (Fiep Bulletin - online, 2014)
This study has as objective, to evaluate the anxiety’s level of the volunteer students currently enrolled in the course of Physical Education. Anxiety can be understood as being an emotional state with psychological and physiological, components, being that, the anxious symptoms are between most common, being able to be found in any person in determined phases of its life (MARKS, 1987). The study was carried through with 46 volunteer students from the course of Physical Education, chosen randomly, not intentionally, out of 184 students. As instrument for the evaluation was applied the Beck Anxiety Inventory (Beck et al., 1988). The questionnaire was tested and retested, test 1 was being applied in the first day of the week, in the arrival of the students and test 2, retest, in the last day of the week, before the students returned home. In relation to the standardized results for Beck, test 1 confirmed that 35.5% of the subjects possess minimum anxiety, 25.8% a light anxiety, 29% a moderate anxiety and 9.7% had serious anxiety. In the retest, the results for minimum anxiety was of 64,5% for the interviewed students, for light anxiety 25.8%, moderate 3.2% and the serious anxiety had a result of 6,5%.